4(a-2)+a=1a-0

Simple and best practice solution for 4(a-2)+a=1a-0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(a-2)+a=1a-0 equation:



4(a-2)+a=1a-0
We move all terms to the left:
4(a-2)+a-(1a-0)=0
We add all the numbers together, and all the variables
4(a-2)+a-(+a)=0
We add all the numbers together, and all the variables
a+4(a-2)-(+a)=0
We multiply parentheses
a+4a-(+a)-8=0
We get rid of parentheses
a+4a-a-8=0
We add all the numbers together, and all the variables
4a-8=0
We move all terms containing a to the left, all other terms to the right
4a=8
a=8/4
a=2

You can always share this solution

See similar equations:

| 4(a-2)+a=0a-3 | | 15=u-9 | | 6x-30-2.50=40 | | 6x-30-2.50=40 | | 6x-30-2.50=40 | | 4(a-2)+a=8a-3 | | 8(e-5)=2)3e-8) | | 4(a-2)+a=3a-2 | | (x)=(x-16) | | 10x+7=39 | | 17d+12=18d | | 117=11w-4 | | 63+4x=75 | | 63+4x=75 | | 63+4x=75 | | 19w+11=11w+11+8w | | 72=3u^2 | | 0.75(x?7)=42 | | 0.75(x?7)=42 | | 0.75(x?7)=42 | | x^2+6=60 | | x^2+6=60 | | x^2+6=60 | | 4(a-2)+a=4a-6 | | 4(a-2)+a=4a-6 | | 80+40+10x=10 | | 1.5(x+8)=45 | | 1.5(x+8)=45 | | e-(18/11)=16/11 | | e-(18/11)=16/11 | | 7x+2.5=-4.5 7x+2.5=-4.5 7x+2.5=-4.5 | | (x?3)(x+5)=84 |

Equations solver categories